The Effects of Cognitive Reading Strategies on Freshman Students’ Reading Comprehension Performance - Worku Seyoum Ketsela (JALL (Journal of Applied Linguistics and Literacy), 2026)
This study discusses the effect of cognitive reading strategy training on freshman students' reading comprehension performance at Addis Ababa University in Ethiopia. Of the 96 participants, 48 were randomly assigned to receive direct strategy instruction in cognitive reading strategies, while the remaining students were exposed to traditional teaching. Data collection was through reading comprehension test and interview. Participants assigned to the experimental group were interviewed immediately after they had taken the cognitive reading strategy test. In this, the interviews provided the researcher with opportunities for deeper explorations of the participants' reading experiences. Descriptive and independent t-tests examined the average pre- and post-test scores between the experimental and control groups, while within-subjects t-tests were conducted within the experimental group. In this research, both groups were tested before and after the study, and perceptions of the strategy training were obtained from the experimental group. This study employed both numerical and descriptive methods; therefore, it is a mixed-methods design. This provides more comprehensive insight into the problem to be investigated; it has the function of compensation for the limitations in using one method to interpret the results. The results indicated that the students who received cognitive strategy training improved significantly in reading comprehension compared to the students in the control group.